Neuropsychological Test Performance of Cognitively Healthy Centenarians: Normative Data From the Dutch 100‐Plus Study. Issue 4 (27th December 2018) - Beker, Nina; Sikkes, Sietske A.M.; Hulsman, Marc; Schmand, Ben; Scheltens, Philip; Holstege, Henne
Abstract : Objectives: The fraction of the population that reaches the age of 100 years is growing. At this age, dementia incidence is high and cognitive functioning is highly variable across individuals. Normative data for neuropsychological tests are lacking in centenarians, which hampers the ability to evaluate their cognitive functioning for both research and clinical practice. Here, we generated norms for neuropsychological tests in a sample of cognitively healthy centenarians while taking sensory impairments into account. Design: Cross‐sectional cohort study. Setting: Centenarians who participate in the prospective 100‐plus Study. Participants: A total of 235 centenarians (71.5% female), who self‐reported to be cognitively healthy, which was confirmed by an informant and a trained researcher. Measurements: We generated normative data for 15 cognitive tests, measuring global cognition (Mini‐Mental State Examination [MMSE]), premorbid intelligence, attention, language, memory, executive function, and visuospatial function by multiple linear regressions and/or by reporting percentiles. Results: Normative data for global cognition resulted in a mean MMSE score of 25.6 ± 3.1 (range = 17‐30; interquartile range = 24‐28). Vision problems and fatigue often complicated the ability to complete tests, and these problems explained 41% and 22% of the missing test scores, respectively. In contrast, hearing problems (4%) and task incomprehension (6%) rarely complicated test performance. While educational level was associated with performance on the majority of the tests, sex and age were only weakly associated with test performance. Conclusions: We generated normative data for 15 common neuropsychological tests in a large sample of cognitively healthy centenarians, while taking age‐related sensory impairments into consideration. These normative data allow the detection of deficits across a wide range of cognitive domains. Our results suggest that, next to education level, vision ability and the level of fatigue should be taken into account when evaluating cognitive functioning in centenarians. J Am Geriatr Soc 67:759–767, 2019.